Implementation of Special Program of Pajale (Rice, Corn and Soybean) in Terara District, East Lombok Regency - Sari, Makdis; Sjah, Taslim (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2016)
The government of Indonesia has targeted self-sufficiency in production of rice, maize, and soybean in a program called âUpsus Pajaleâ (Special effort for increasing production of rice, maize, and soybean). This paper aims to describe the implementation of âPajaleâ program by farmers, problem, and kinds of actives in the program. Result of this study reveals that there was an improvement in the production of rice, yet there were problems at both farmers and extensions worker. Recommendation for this study are that supervision need to be beginner at the start of the season for better duty implementation, and supervisorâs salary need to be increased for improving working motivation.